Research on interaction and trust theory model for cockpit human-machine fusion intelligence - Duan, Ya; Cai, Yandong; Peng, Ran; Zhao, Hua; Feng, Yue; You, Xiaolong (Frontiers in Neuroscience, 2024)
Based on Boyd's "OODA" aerial combat theory and the principles of operational success, an analysis of the operational division patterns for cross-generational human-machine collaboration was conducted. The research proposed three stages in the development of aerial combat human-machine fusion intelligence: "Human-Machine Separation, Functional Coordination," "Human-Machine Trust, Task Coordination," and "Human-Machine Integration, Deep Fusion." Currently, the transition from the first stage to the second stage is underway, posing challenges primarily related to the lack of effective methods guiding experimental research on human-machine fusion interaction and trust. Building upon the principles of decision neuroscience and the theory of supply and demand relationships, the study analyzed the decision-making patterns of human-machine fusion intelligence under different states. By investigating the correlations among aerial combat mission demands, dynamic operational limits of human-machine tasks, and aerial combat mission performance, a theoretical model of human-machine fusion interaction and trust was proposed. This model revealed the mechanistic coupling of human-machine interactions in aerial tasks, aiming to optimize the decision-making processes of human-machine systems to enhance mission performance. It provides methodological support for the design and application of intelligent collaborative interaction modes in aviation equipment.